2018
DOI: 10.1002/gj.3195
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal profile of the Upper Weihe River: Evidence for the late Cenozoic uplift of the northeastern Tibetan Plateau

Abstract: The Upper Weihe River (UP‐WHR) basin is located along the northeastern Tibetan Plateau. With the northeastward expansion of the Tibetan Plateau since the late Cenozoic, it has involved foreland propagation and undergone obvious surface uplift. In order to determine the latest differential rock uplift and river incision, longitudinal profiles for 12 major tributaries of the UP‐WHR were extracted. Among them, 11 tributaries display uneven profiles with “slope‐break” knickpoints, suggesting that they are in a tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The cosmic nuclide dating result on the highest terrace in the Xiangshan–Tianjingshan fault zone was reported to be 2.4 Ma, which might represent the transformation age from thrusting to left‐lateral strike‐slip faulting (Zhang & Cai, 2006), consistent with the aforementioned result. The palaeochannel reconstruction along the north margin of the Qinling shows that the tributaries along its north margin have a higher incision of 144 ± 25 m since the late Early Pleistocene (~1.4–1.2 Ma), leading to the break‐ up of the Tianshui ancient lake (Shi et al, 2018), which also dominates the intensive north‐eastward expansion of the Tibetan Plateau.…”
Section: Discussionmentioning
confidence: 99%
“…The cosmic nuclide dating result on the highest terrace in the Xiangshan–Tianjingshan fault zone was reported to be 2.4 Ma, which might represent the transformation age from thrusting to left‐lateral strike‐slip faulting (Zhang & Cai, 2006), consistent with the aforementioned result. The palaeochannel reconstruction along the north margin of the Qinling shows that the tributaries along its north margin have a higher incision of 144 ± 25 m since the late Early Pleistocene (~1.4–1.2 Ma), leading to the break‐ up of the Tianshui ancient lake (Shi et al, 2018), which also dominates the intensive north‐eastward expansion of the Tibetan Plateau.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that the horizontal and vertical displacements induced by the latest earthquake were about 3.5 and 1.7 m, respectively [47]. During the late Quaternary, the northwest margin of the Qianhe Graben featured a horizontal slip rate of 1-3 mm/year and a vertical slip rate of 0.9 mm/year, while the southeastern margin featured a horizontal slip rate of 2-3 mm/year and a vertical slip rate of 0.2-0.5 mm/year [48] (Figure 1). Although more detailed field work has been conducted here along the strike and fault scarps of QBF [49,50], there is no more evidence to show the Quaternary activity during the late Quaternary, indicating that the QBF is a concealed fault.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…(a), (b), (c), and (d) are the regions of interest. The horizontal and vertical slip rates were collected from [48]. All data were reprojected into WGS_1984_UTM_Zone_48N, and the datum was D_WGS_1984.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…New tectonic movements form the topographical conditions required for lakes to accommodate water bodies, which is conducive to the formation of lakes. Local and sudden faults may also change the pattern of rivers and lakes, such as barrier lake formation and changes in river direction after earthquakes (Jia et al 2012; Shi et al 2018). Simultaneously, geological movements lead to different geographical distribution characteristics of environments (geomorphology, climate, hydrology, soil, vegetation), such as latitudinal zonality, dry‐humidity zoning, vertical banding, and nonzonality, which is the natural exogenous force affecting the evolution and spatial pattern of rivers and lakes (Li et al 2012; Gu et al 2016).…”
Section: Drivers Of Hc Weaknessmentioning
confidence: 99%